Observaciones sobre la biología de melolóntidos (Coleoptera: Scarabaeoidea) en una localidad de los Altos de Chiapas, México. - Gómez, Benigno; Villalobos, Francisco Javier; Ruíz, Lorena; Castro, Adriana E. (Instituto de Ecología, A.C., 1999)
Observations on the biology of a community of scarab larvae and adult beetles (Coleóptera: Melolonthidae) in a locality of Los Altos de Chiapas, México are presented. Collections of both stages were made during the preparation and plant growing season of cornfields, oak-pine surroundings and cloud forest patches (March to July of 1997). Eight species were collected, being Phyllophaga obsoleta and Anómala atomograma the most conspicuous during the larval and adult stages. Considering their abundances, these may be related with damage in cornfields. Three probably new species of Phyllophaga were collected and their larvae seem to be mostiy associated with forest soils. A new altitude record for Cyclocephala alexi is registered. Hoplia mexicana is cited for the first time with precisión from a locality of México.